A review of actinic keratosis, skin field cancerisation and the efficacy of topical therapies. (25th August 2020) - Sinclair, Robert; Baker, Christopher; Spelman, Lynda; Supranowicz, Madeleine; MacMahon, Beth
Abstract: While a wide range of treatments exist for actinic keratosis and skin field cancerisation, the long‐term benefits of the most common topical therapies are poorly defined. This report reviews the efficacy of the most commonly used topical therapies to treat regional or field lesions. Limited clinical and histopathological data are available on clearance rates at 12 months post‐treatment for the most commonly used agents, with varied outcome measures making any comparison difficult. In general, total field clearance rates at 12 months are suboptimal for the most commonly employed agents. Given the increasing incidence of actinic keratosis and skin field cancerisation due to an ageing population, further research into the efficacy of therapies is critical to guide treatment choice.